KEEFEKTIFAN PEMBELAJARAN MENULIS CERITA FANTASI DENGAN MODEL PEMBELAJARAN MEANINGFUL LEARNING DAN JOYFUL LEARNING BERBANTUAN MEDIA FILM PENDEK PADA KELAS VII DI SMP NEGERI 13 SEMARANG - Novi Fitriani; Zuliyanti Zuliyanti (Universitas Batanghari, 2026)
The background of this study is the tendency of students to experience difficulties in developing ideas and conflicts, organizing the plot and structure of stories, and developing their imagination in fantasy stories. This study aims to determine the effectiveness and compare the effectiveness of the Meaningful Learning and Joyful Learning models assisted by short films in teaching fantasy writing. This study uses a quantitative approach with a quasi-experimental design through a nonequivalent control group design. Data were obtained from pretest and posttest scores, supported by observations and interviews. Data collection was conducted through written tests, observations, and interviews. Data analysis techniques were performed using statistical tests, including normality tests, homogeneity tests, Paired Sample t-tests, N Gain, and Independent Sample t-tests. The results showed that the N-Gain percentage calculation for the Meaningful Learning model assisted by short films obtained an average score of 56.7200%, while the Joyful Learning model assisted by short films obtained an average score of 58.8033%. These results indicate that both learning models have a moderate level of effectiveness and are classified as quite effective. In conclusion, both models are classified as quite effective for use in teaching fantasy story writing.